SOS Chrétiens d’Orient : le renouveau du conservatisme catholique français au prisme de l’Orient - Alexis Artaud de La Ferrière (Les Cahiers d’EMAM)
For the past several years, the plight of Christian communities in the Near East has captured the interest of the French public. Emerging from this public interest, SOS Chrétiens d’Orient was founded in 2013. However, this new NGO quickly courted controversy because of its dual orientation, as both an international development organisation and as a hub for conservative socio-political action in France. How should we make sense of this dual identity? What ideals undergird SOS Chrétiens d’Orient? How does the organisation aim to operationalize those ideals? Based on research carried out between June 2017 and June 2019, this articles addresses seeks to answer these questions.